2017
DOI: 10.6017/ihe.2017.91.10139
|View full text |Cite
|
Sign up to set email alerts
|

The Slow Path to General Education in Chinese Universities

Abstract: In recent years, many Chineseuniversities have launched general educationprograms. This piece explores the history of general education in China and outlines innovative gen ed programs in development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Pan Jing believes that the core of the "Double First-class" construction is the construction of first-class disciplines, and analyzed the action framework under this guidance [2]. In addition, there are studies on the construction target [3], construction idea [4,5] and promotion strategy [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pan Jing believes that the core of the "Double First-class" construction is the construction of first-class disciplines, and analyzed the action framework under this guidance [2]. In addition, there are studies on the construction target [3], construction idea [4,5] and promotion strategy [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…About a month and a half after the epidemic began, nearly 270 million students and 20 million teachers participated in online teaching and learning, making it the largest number of educational activities conducted online. During the pandemic, Dunrong and Jin (2020) reported that the unplanned educational disruptions affected its 2,688 higher education institutions due to their offline operational suspension. In line with these localised closures, China's Ministry of Education developed a smart virtual learning environment to transform physical classes to online spaces (Jiang et al, 2023).…”
Section: The Surge Of E-learning In Chinamentioning
confidence: 99%
“…Postgraduates with good AD actively participate in scientific research training and taking courses, and show strong scientific research ability [8]. Graduate students with good AD are more successful in their academic development, and are more likely to choose academic careers in the future [9].…”
Section: Introductionmentioning
confidence: 99%